Characterizing the Molecular Pathology of Arrhythmogenic Cardiomyopathy in Patient Buccal Mucosa Cells. (February 2016) - Asimaki, Angeliki; Protonotarios, Alexandros; James, Cynthia A.; Chelko, Stephen P.; Tichnell, Crystal; Murray, Brittney; Tsatsopoulou, Adalena; Anastasakis, Aris; te Riele, Anneline; Kléber, André G.; Judge, Daniel P.; Calkins, Hugh; et al.
Abstract : Background—: Analysis of myocardium has revealed mechanistic insights into arrhythmogenic cardiomyopathy but cardiac samples are difficult to obtain from probands and especially from family members. To identify a potential surrogate tissue, we characterized buccal mucosa cells. Methods and Results—: Buccal cells from patients, mutation carriers, and controls were immunostained and analyzed in a blinded fashion. In additional studies, buccal cells were grown in vitro and incubated with SB216763. Immunoreactive signals for the desmosomal protein plakoglobin and the major cardiac gap junction protein Cx43 were markedly diminished in buccal mucosa cells from arrhythmogenic cardiomyopathy patients with known desmosomal mutations when compared with controls. Plakoglobin and Cx43 signals were also reduced in most family members who carried disease alleles but showed no evidence of heart disease. Signal for the desmosomal protein plakophilin-1 was reduced in buccal mucosa cells in patients with PKP2 mutations but not in those with mutations in other desmosomal genes. Signal for the desmosomal protein desmoplakin was reduced in buccal mucosa cells from patients with mutations in DSP, DSG2, or DSC2 but not in PKP2 or JUP . Abnormal protein distributions were reversed in cultured cells incubated with SB216763, a small molecule that rescues the disease phenotype in cardiac myocytes. Conclusions—: Buccal mucosa cells from arrhythmogenic cardiomyopathy patients exhibit changes in the distribution of cell junction proteins similar to those seen in the heart. These cells may prove useful in future studies of disease mechanisms and drug screens for effective therapies in arrhythmogenic cardiomyopathy. Abstract : Supplemental Digital Content is available in the text.